2008
DOI: 10.1534/genetics.107.082479
|View full text |Cite
|
Sign up to set email alerts
|

Both Costs and Benefits of Sex Correlate With Relative Frequency of Asexual Reproduction in Cyclically ParthenogenicDaphnia pulicariaPopulations

Abstract: Sexual reproduction is generally believed to yield beneficial effects via the expansion of expressed genetic variation, which increases the efficiency of selection and the adaptive potential of a population. However, when nonadditive gene action is involved, sex can actually impede the adaptive progress of a population. If selection promotes coupling disequilibria between genes of similar effect, recombination and segregation can result in a decrease in expressed genetic variance in the offspring population. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Briefly, based on the average frequency of males and ephippial females found in each population over a three‐year sampling period (1999, 2000, and 2001), the investment in sex per population was estimated as: Cloverdale 18%, Little Long 15%, Bristol 3.5%, Warner 1.5%, Pine 0.6%, and Baker 0.5%. The consistency of these frequency of sex estimates is supported anecdotally by our own sampling during 2002–2005 (Allen and Lynch 2008). We sampled these lakes repeatedly during the peak periods of sexual reproduction (late May/June) to collect ephippial females (individuals that had already reproduced sexually).…”
Section: Methodssupporting
confidence: 59%
“…Briefly, based on the average frequency of males and ephippial females found in each population over a three‐year sampling period (1999, 2000, and 2001), the investment in sex per population was estimated as: Cloverdale 18%, Little Long 15%, Bristol 3.5%, Warner 1.5%, Pine 0.6%, and Baker 0.5%. The consistency of these frequency of sex estimates is supported anecdotally by our own sampling during 2002–2005 (Allen and Lynch 2008). We sampled these lakes repeatedly during the peak periods of sexual reproduction (late May/June) to collect ephippial females (individuals that had already reproduced sexually).…”
Section: Methodssupporting
confidence: 59%
“…Most of the studies listed in Table 2 used populations that were newly isolated from the field to capture natural genetic variation (discussed below). But evaluation of the effect of sex on fitness took place under laboratory conditions (Charlesworth & Charlesworth, 1975;Deng & Lynch, 1996;Pfrender & Lynch, 2000;Allen & Lynch, 2008). This approach creates potential problems because consequences of breaking down associations were tested in a different context than where associations were developed (Agrawal, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…The propensity of sex and the apparent ephemerality of asexuality have remained enigmatic problems in evolutionary biology despite over a century of research on the subject (Weismann, 1889; Otto, 2009). Many researchers proposed that the processes of meiotic recombination and segregation generate and maintain genetic variation within sexual populations, increasing the rate of adaptive evolution (Weismann, 1889; Lynch and Deng, 1994; Charlesworth and Charlesworth, 1995; Allen and Lynch, 2008; Lively, 2010). Theories showed that the effects of sexual reproduction can be more complex, however, with possible increases or decreases in genetic variation over one (short‐term) to many generations (long‐term) (Charlesworth et al, 1993; Lynch and Deng, 1994; Charlesworth and Pannell, 2001; Barton and Otto, 2005; Agrawal, 2006; Keightley and Otto, 2006).…”
mentioning
confidence: 99%